Does nutrient enrichment compensate fungicide effects on litter decomposition and decomposer communities in streams? - Fernández, Diego (2016)
Nutrient and pesticide pollution are widespread agricultural stressors. Fungicides may affect freshwater fungi, which play an important role in litter decomposition (LD), whereas moderate nutrient enrichment can stimulate LD. We examined potential interaction effects of nutrients and fungicides on decomposer communities and LD in a 14-day two-factorial (fungicide and nutrient treatments) mesocosm experiment. Fungicide exposure was limited to 4 days to simulate episodic contamination. Only the microbial community responded significantly to the experimental factors, though non-significant increases >20% were found for invertebrate decomposer weight gain and LD under high-nutrient conditions. Fungal community structure responded more strongly to fungicides than sporulation. Sporulation responded strongest to nutrients. Bacterial community structure was affected by both factors, although only nutrients influenced bacterial density. Our results suggest effects from fungicides at field-relevant levels on the microbial community. Whether these changes propagate to invertebrate communities and LD remains unclear and should be analysed under longer and recurrent fungicide exposure. (C) 2016 Elsevier B.V. All rights reserved.